2016
DOI: 10.2106/jbjs.15.00340
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Blood Metal Ions in Identifying Patients with Unilateral Birmingham Hip Resurfacing and Corail-Pinnacle Metal-on-Metal Hip Implants at Risk of Adverse Reactions to Metal Debris

Abstract: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 39 publications
5
56
0
Order By: Relevance
“…Furthermore, in the occupational setting, an established relationship exists between high metal ion exposure and the development of certain cancers [ 12 ]. Although there is a theoretical increased risk of cancer in all patients receiving hip replacement, MoM hip replacements produce much higher concentrations of metal ions in the blood compared with conventional hip replacements, especially if the MoM hip replacement is not functioning optimally [ 21 , 22 ]. Hexavalent chromium (Cr 6+ ) is a known carcinogen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the occupational setting, an established relationship exists between high metal ion exposure and the development of certain cancers [ 12 ]. Although there is a theoretical increased risk of cancer in all patients receiving hip replacement, MoM hip replacements produce much higher concentrations of metal ions in the blood compared with conventional hip replacements, especially if the MoM hip replacement is not functioning optimally [ 21 , 22 ]. Hexavalent chromium (Cr 6+ ) is a known carcinogen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies identified implant-specific blood metal ion thresholds in patients who had undergone unilateral or bilateral Birmingham Hip Resurfacing (BHR; Smith & Nephew) or unilateral Corail-Pinnacle total hip replacement (DePuy) 14 , 15 . These designs are 2 of the most commonly implanted MoM hip devices worldwide 3 , 16 , 17 .…”
mentioning
confidence: 99%
“…Medicines and Healthcare products Regulatory Agency (MHRA) (7 μg/L for both cobalt and chromium) 5 and by experts in the U.S. (3 μg/L and 10 μg/L for both cobalt and chromium) 18 . Investigators who used the new implant-specific thresholds 14 , 15 missed fewer patients with ARMD than when they used the fixed thresholds proposed by regulatory authorities 5 , 18 . The implant-specific thresholds were derived in a large patient cohort (n = 783) and appear to be useful when managing patients with these particular MoM implant designs 14 , 15 .…”
mentioning
confidence: 99%
“…In addition, levels may be measured from serum, whole blood, or erythrocytes [13] and there is no conversion factor for these values as the intracellular and extracellular compartments act independently of each other [14]. Cobalt and chromium levels, or cobalt levels alone, may be used to identify patients at risk of adverse reactions to metal debris [15]. …”
Section: Discussionmentioning
confidence: 99%